Reducing voltage fluctuations using DSTATCOMs and reactive power of PV inverters in a medium voltage distribution system - Duong Quoc Hung; Yateendra Mishra; Geoffrey Walker (The Journal of Engineering, 2019)
This paper proposes local reactive power control to mitigate the voltage fluctuation in medium-voltage systems using DSTATCOMs and photovoltaic (PV) inverters. New expressions are developed to estimate voltage fluctuations and reactive power compensations by transforming line segment power-flow variables into nodal power injections. Using local measurements of voltages and solar powers, the method can provide a fast estimation of reactive power compensations to maintain the voltage at every bus. DSTATCOMs are also properly allocated to enhance the voltage controllability. Coordinated control of multiple reactive power resources is investigated as well. One-second solar irradiance along with one-minute home loads is used to demonstrate the effectiveness of the proposed method.